Evaluation Study of Role of Voluntary Agencies in the Implementation of Social Welfare Programmes (Design, Schedules etc. and Instructions) - Planning Commission (Planning Commission, 1970)
Voluntary agencies had been rendering valuable service in the field of social welfare path the support of philanthropists and the local community. Their importance in the field of social welfare services was recognised by the planners and some provision was, therefore, made in the Five Year Plans to strengthen and widen the scope of their activities. The trust so placed in them was mainly due to two important reasons Firstly, it was felt, that these agencies had a background of considerable experience in the organisation and conduct of welfare programmes and could react more quickly to changing social needs than could be expected of the official machinery.
Programme Evaluation Organisation Planning Commission Government of India